Ebola VP40 in Exosomes Can Cause Immune Cell Dysfunction - Pleet, Michelle L.; Mathiesen, Allison; DeMarino, Catherine; Akpamagbo, Yao A.; Barclay, Robert A.; Schwab, Angela; Iordanskiy, Sergey; Sampey, Gavin C.; Lepene, Benjamin; Ilinykh, Philipp A.; Bukreyev, Alexander; Nekhai, Sergei; et al. (Frontiers in Microbiology, 2016)
Ebola virus (EBOV) is an enveloped, ssRNA virus from the family Filoviridae capable of causing severe hemorrhagic fever with up to 80-90% mortality rates. The most recent outbreak of EBOV in West Africa starting in 2014 resulted in over 11,300 deaths; however, long-lasting persistence and recurrence in survivors has been documented, potentially leading to further transmission of the virus. We have previously shown that exosomes from cells infected with HIV-1, HTLV-1 and Rift Valley Fever virus are able to transfer viral proteins and non-coding RNAs to naïve recipient cells, resulting in an altered cellular activity. In the current manuscript, we examined the effect of Ebola structural proteins VP40, GP, NP and VLPs on recipient immune cells, as well as the effect of exosomes containing these proteins on naïve immune cells. We found that VP40-transfected cells packaged VP40 into exosomes, and that these exosomes were capable of inducing apoptosis in recipient immune cells. Additionally, we show that presence of VP40 within parental cells or in exosomes delivered to naïve cells could result in the regulation of RNAi machinery including Dicer, Drosha, and Ago 1, which may play a role in the induction of cell death in recipient immune cells. Exosome biogenesis was regulated by VP40 in transfected cells by increasing levels of ESCRT-II proteins EAP20 and EAP45, and exosomal marker proteins CD63 and Alix. VP40 was phosphorylated by Cdk2/Cyclin complexes at Serine 233 which could be reversed with r-Roscovitine treatment. The level of VP40-containing exosomes could also be regulated by treated cells with FDA-approved Oxytetracycline. Additionally, we utilized novel nanoparticles to safely capture VP40 and other viral proteins from Ebola VLPs spiked into human samples using SDS/reducing agents, thus minimizing the need for BSL-4 conditions for most downstream assays. Collectively, our data indicates that VP40 packaged into exosomes may be responsible for the deregulation and eventual destruction of the T-cell and myeloid arms of the immune system (bystander lymphocyte apoptosis), allowing the virus to replicate to high titers in the immunocompromised host. Moreover, our results suggest that the use of drugs such as Oxytetracycline to modulate the levels of exosomes exiting